2014
DOI: 10.5812/ircmj.16323
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Insulin-Like Growth Factor-1 Gene Therapy and Cell Transplantation on Rat Acute Wound Model

Abstract: Background:Wound healing is a complex process. Different types of skin cells, extracellular matrix and variety of growth factors are involved in wound healing. The use of recombinant growth factors in researches and production of skin substitutes are still a challenge.Objectives:Much research has been done on the effects of gene therapy and cell therapy on wound healing. In this experimental study, the effect of insulin-like growth factor (IGF-1) gene transfer in fibroblast cells was assessed on acute dermal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
(43 reference statements)
0
4
0
1
Order By: Relevance
“…e IGF family is expected to have an essential role in regulating cell proliferation, apoptosis, and transformation [11]. IGF1, widely regarded as a circulating growth factor, is normally produced by the liver and participates in mediating body growth through growth hormone e ects [40], but it is fatal for the normal development and growth of cell maintenance and homeostasis [9].…”
Section: Discussionmentioning
confidence: 99%
“…e IGF family is expected to have an essential role in regulating cell proliferation, apoptosis, and transformation [11]. IGF1, widely regarded as a circulating growth factor, is normally produced by the liver and participates in mediating body growth through growth hormone e ects [40], but it is fatal for the normal development and growth of cell maintenance and homeostasis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results indicated that wounded skin treated with EFA had higher local IGF-1 mRNA expression throughout the experiment, which may benefit the wound healing outcome. Gene therapy with the IGF-1 gene transferred to fibroblasts was found to upregulate the expression of IGF-1 and improve wound healing outcome [33].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 is a growth factor produced by fibroblasts and other epithelial cells, and it plays an important role in re-epithelialization and granulation tissue formation during the wound healing process [ 32 ]. One of its roles is vascular endothelial insulin/IGF-1 signaling in the homeostasis of the skin vasculature and in neovascularization on the skin during wound healing [ 33 ].…”
Section: Discussionmentioning
confidence: 99%